Cross-sectional small intestinal surveillance of maintenance hemodialysis patients using video capsule endoscopy: SCHEMA study - Hosoe, Naoki; Matsukawa, Shigeaki; Kanno, Yoshihiko; Naganuma, Makoto; Imaeda, Hiroyuki; Ida, Yosuke; Tsuchiya, Yoshitsugu; Hibi, Toshifumi; Ogata, Haruhiko; Kanai, Takanori (Endoscopy International Open, 2016)
Background and study aims: Small intestinal pathology in hemodialysis (HD) patients has been studied in only a small number of retrospective case series. One method for noninvasively surveying small intestinal disorders is video capsule endoscopy (VCE). The primary aim of this study was to investigate the prevalence of small intestinal abnormalities among asymptomatic maintenance HD outpatients using VCE. The secondary aim was to assess the clinical impact of these abnormalities.Patients and methods: This study consisted of two phases. In phase I, a cross-sectional study, a cohort of patients who received maintenance HD three times weekly at an outpatient hemodialysis clinic were studied using VCE. Phase II was a prospective cohort study with follow up for 1 year after VCE. Results: Fifty-six patients were enrolled in this study, and two were excluded from analysis due to capsule retention in the stomach. The prevalence of small bowel abnormalities in HD patients was 64.8 % (35/54) (95 % confidential interval 52.1 % – 77.6 %). Of 54 patients, 21 (38.9 %) had mucosal lesions, 10 (18.5 %) had vascular lesions, and 4 (7.4 %) had both lesion types. During the 1-year follow-up period, events occurred in four patients. A small bowel-associated event was observed in one patient, who underwent laparoscopy-assisted small intestinal partial resection 3 months after diagnosis by VCE. All patients in whom events were seen had small bowel abnormalities; no events were observed in the VCE-negative group.Conclusions: Although asymptomatic maintenance HD patients had a high prevalence of small bowel abnormalities (64.8 %), they did not have a high incidence of small bowel-associated events during the 1-year follow-up.